Fermentation Products of Paenibacillus bovis sp. nov. BD3526 Alleviates the Symptoms of Type 2 Diabetes Mellitus in GK Rats - Qiao, Zhenyi; Han, Jin; Feng, Huafeng; Zheng, Huajun; Wu, Jiang; Gao, Caixia; Yang, Meng; You, Chunping; Liu, Zhenmin; Wu, Zhengjun (Frontiers in Microbiology, 2019)
Gut microbiota is closely related to type 2 diabetes mellitus (T2DM). The gut microbiota of patients with T2DM is significantly differed from that of healthy subjects in terms of bacterial composition and diversity. Here, we used the metabolites of Paenibacillus bovis sp. nov. BD3526 to study the disease progression of T2DM (Goto-kakisaki, GK) rats. We found that the symptoms in GK rats fed the metabolites of BD3526 were significantly improved. 16S rRNA sequencing showed that the metabolites of BD3526 had strong effects on the gut microbiota by increasing the content of Akmenmansia. In addition, the interaction of genus in the gut of BD3526 group also changed significantly. Further cytokine detection revealed that the metabolites of BD3526 can reduce the inflammatory factors in the intestinal mucus of GK rats, thereby inhibiting the inflammatory response and ameliorate the symptoms of T2DM.